O conceito de encarnação no horizonte teológico de Joseph Moingt - Alves, Renato Gomes (2018)
This dissertation contemplates an investigation into the scope and unfolding of the concept of incarnation on the theological horizon of contemporary french theologian Joseph Moingt. The object of study, the concept of incarnation, is seen with the proper look of theology, in order to contribute to respond to the challenges of contemporary times. Moingt's academic career is long and vast. Between professor and researcher, he publishes a great number of books and articles that the present research is worth as a field to be unfolded, in order to bring new understandings to christology and indicate new possibilities of action in the contemporary world. The hypothesis of research is based on the way in which Moingt presents the concept of incarnation, recovering in the evangelical narratives the story of Jesus of Nazareth. The old dogmatic formulation proves incapable of responding to the demands of evangelization of the present time. For this reason, the resumption of apostolic kerygma and the return to the announce based on resurrection show that contemporary christology needs a new foundation and new method, which should no longer be attached to the dictates of dogma, nor do they exclude the truth revealed in Christ. For this purpose, a first flight over the theological horizon of Moingt is carried out in a discursive and descriptive way, from works translated into portuguese. Next, the concept of incarnation appears as the central object of study. Fruit of the dogmatic reflection of the first centuries, the development of the idea of incarnation is seen in the unfolding of the history until arriving at the contemporaneity, where will be seen of more detailed way in the work of the french theologian. However, the best understanding of the conceptual extension will be through the practical unfolding of three specific axes: the Spirit, the Church, and the signs of the times, which denote the incarnation for the redemption of man. The results of this research point to the practice of humanization that the incarnation provides. The recovery of redemptive action, such as the promotion of full life, is the great call that systematic reflection promotes. The journey that begins with the restorative practice reveals the practical understanding of the christological dogma of the incarnation. And although in a different context, Joseph Moingt's reflection provides a return to the narrative, rich not in words, but in humanizing actions that reveal the authentic face of Jesus Christ